2021
DOI: 10.1111/dth.15036
|View full text |Cite
|
Sign up to set email alerts
|

Systemic hedgehog inhibitors to treat locally advanced basal cell carcinomas of the head–neck region: A retrospective study

Abstract: Basal cell carcinoma (BCC) is the most commonly diagnosed human cancer, typically occurring in faired-skin subjects over 50 years old.Although it could occur in multiple locations, 80% of the patients pre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In this trial, the OR for patients treated with sonidegib was 81% ( n = 17; 95% CI 60–95%) including 6 (29%) patients with a complete response (CR). These observations are consistent with earlier findings from the long-term 30-month analysis of the pivotal phase II BOLT study and recently published 42-month analysis with an OR of 74.2% per investigator review using RECIST-criteria and the reported OR of 76.8% in a retrospective case series conducted in 13 patients ( 14 , 19 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this trial, the OR for patients treated with sonidegib was 81% ( n = 17; 95% CI 60–95%) including 6 (29%) patients with a complete response (CR). These observations are consistent with earlier findings from the long-term 30-month analysis of the pivotal phase II BOLT study and recently published 42-month analysis with an OR of 74.2% per investigator review using RECIST-criteria and the reported OR of 76.8% in a retrospective case series conducted in 13 patients ( 14 , 19 ).…”
Section: Discussionsupporting
confidence: 92%
“…To date, several clinical cases have been published, demonstrating sonidegib’s rapid activity and great tolerance, but larger sample size clinical investigations are required to validate these findings in clinical practice ( 17 19 ). The current study is the first conducted in patients with laBCC treated with 200 mg in real life.…”
Section: Discussionmentioning
confidence: 99%